Continuum of maternal health care utilisation in Sub-Saharan African countries: A positive deviance approach - Samrawit Mihret Fetene; Melaku Birhanu Alemu; Elsa Awoke Fentie; Tsegaye G. Haile (PLoS ONE, 2025)
Introduction Maternal health is a global priority for achieving Sustainable Development Goal 3.1. However, many mothers in Africa still lack access to the full continuum of care for maternal health (continuum of care). The lowest coverage is often observed among underserved mothers, particularly those who are uneducated and from poor households. Despite these disadvantages, some mothers in every community find effective ways to access a better continuum of care – these are known as positive deviants. However, there is limited evidence to support this concept. Therefore, this study examined the determinants of continuum of health care utilisation among underserved mothers in sub-Saharan African countries. Methods Data from the Demographic and Health Surveys of 15 Sub-Saharan African countries with high maternal mortality ratio were used. A positive deviance approach was applied to identify 32,778 underserved mothers using a two-stage stratified sampling technique for the final analysis. A multilevel mixed-effect binary logistic regression analysis was conducted to identify factors associated with being a positive deviant. Finally, an adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to declare statistically significant determinants. Results The overall continuum of care utilisation among underserved mothers was 13.8% (95% CI: 13.5–14.2%). Underserved mothers who were employed (AOR = 1.2; 95% CI: 1.1–1.3), those who had educated husband (AOR = 1.3; 95% CI:1.2–1.4), had one to three children (AOR = 1.2; 95%CI: 1.1–1.3), had a history of pregnancy termination (AOR = 1.3; 95%CI: 1.1–1.4), had the healthcare decision making autonomy (AOR = 1.2; 95% CI: 1.1–1.3), and faced no barriers to accessing health services (AOR = 1.2; 95% CI: 1.0–1.2) were significantly associated with being a positive deviant. Conclusion Despite socioeconomic disadvantage, a subset of underserved mothers in sub-Saharan Africa successfully utilised the full continuum of maternal healthcare. Key enabling factors included maternal employment, partner education, smaller family size, prior pregnancy termination, autonomy in healthcare decision-making, and absence of access barriers. These findings support the positive deviance approach as a valuable lens for identifying actionable pathways to improve maternal health coverage. Interventions that amplify these enabling factors could help close equity gaps and accelerate progress toward maternal health targets in high-burden settings.